Efectos del tratamiento de ortodoncia en la imagen del cuerpo y en la autoestima de los adolescentes (2003)
ABSTRACT: The purpose of this research project was to inquire about the eventual influence of the orthodontic treatment on the body's image and self-esteem of adolescents. The universe of our sample consisted of adolescents who consulted at the School of the Dentistry of the University of Antioquia in search of resolving their malocclusion and their body problems; nine of the attendants participated as volunteers, contributing to the research project with their personal account. The participants were interviewed twice, keeping in mind the following analysis categories that directed the research project: body - organism, complain - demand and narcissism - self-esteem. The findings showed that each complaint that the adolescents makes to the orthodontist regarding something specific that affects his or her physical organism - the malocclusion -, is generally directed by a demand related to their body. Also, that the self-esteem increment as a result of the treatment -if reached - can only be achieved in a temporary manner.